Are the Cognitive Alterations Present in Children Born From Preeclamptic Pregnancies the Result of Impaired Angiogenesis? Focus on the Potential Role of the VEGF Family - Lara, Evelyn; Acurio, Jesenia; Leon, José; Penny, Jeffrey; Torres-Vergara, Pablo; Escudero, Carlos (Frontiers in Physiology, 2018)
Evidence from clinical studies has proposed that children born from preeclamptic women have a higher risk of suffering neurological, psychological or behavioral alterations. However, to date, the mechanisms behind these outcomes are poorly understood. Here we speculate that the neurodevelopmental alterations in the children of preeclamptic pregnancies result from impaired angiogenesis. The pro-angiogenic factors vascular endothelial growth factor (VEGF) and placental growth factor (PlGF) are key regulators of both vascular and neurological development, and it has been widely demonstrated that umbilical blood of preeclamptic pregnancies contains high levels of soluble VEGF receptor type 1 (sFlt-1), a decoy receptor of VEGF. As a consequence, this anti-angiogenic state could lead to long-lasting neurological outcomes. In this non-systematic review, we propose that alterations in the circulating concentrations of VEGF, PlGF and sFlt-1 in preeclamptic pregnancies will affect both fetal cerebrovascular function and neurodevelopment, which in turn may cause cognitive alterations in post-natal life.